Hemophagocytic lymphohistiocytosis presenting in a patient with human immunodeficiency virus and reactivated Hepatitis B infection. (2022) - Chen, David T.; Patel, Imari; Cabral, Stephanie; Chintalapati, Sai; Iddings, Aaron; Patel, Devang
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare clinical syndrome of inappropriate immune activation which can present at any age and is commonly associated with other conditions of either excessive or impaired immune response, such as malignancy, infection, autoimmunity or immunodeficiency. In cases associated with human immunodeficiency virus (HIV) infection, an additional trigger such as acute infection or malignancy is frequently identified. We report a case of HLH presenting in a patient with uncontrolled HIV and reactivated hepatitis B infection, which to our knowledge has only been reported once before. Given challenges with diagnosis and its life-threatening course, HLH is an important consideration especially in critically ill patients with underlying HIV and nonspecific presentations such as fevers, cytopenias and encephalopathy.